1994
DOI: 10.1046/j.1471-4159.1994.63020465.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of the Human Platelet Serotonin 5‐HT2A Receptor: Identity with Frontal Cortex Serotonin 5‐HT2A Receptor

Abstract: Previous radioligand binding studies have demonstrated human platelet serotonin2A (5‐HT2A) receptor binding sites. Pharmacological similarities between platelet and frontal cortex 5‐HT2A receptor binding parameters have been demonstrated. However, it is not clear whether the platelet 5‐HT2A receptor primary structure is identical to that of the brain receptor. Three overlapping cDNAs were obtained to span completely the coding region of the 5‐HT2A receptor. These clones were sequenced with external and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(38 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…As far as pedophilia is related to ICD and violence/aggression (see Introduction), our findings are in agreement with previous reports on increased number of platelet 5-HT2A receptors in aggression . The platelet 5-HT2A receptor is essentially identical to the corresponding structure in central 5-HT synapses (Cook et al 1994). However, other studies reported no significant association between platelet 5-HT2A receptor sites and measures of aggression (McBride et al 1994), whereas Blumensohn et al (1995) reported a reduction in the number of platelet 5-HT2A binding sites in delinquent adolescents.…”
Section: Discussionmentioning
confidence: 86%
“…As far as pedophilia is related to ICD and violence/aggression (see Introduction), our findings are in agreement with previous reports on increased number of platelet 5-HT2A receptors in aggression . The platelet 5-HT2A receptor is essentially identical to the corresponding structure in central 5-HT synapses (Cook et al 1994). However, other studies reported no significant association between platelet 5-HT2A receptor sites and measures of aggression (McBride et al 1994), whereas Blumensohn et al (1995) reported a reduction in the number of platelet 5-HT2A binding sites in delinquent adolescents.…”
Section: Discussionmentioning
confidence: 86%
“…32 In addition, primers were not designed within known polymorphic coding regions such as for the 5ht2a and 5ht6 receptors. 64,65 Given the existence of multiple isoforms of the a1a receptor, 66 primers that were specific for this subtype but did not pertain to a particular isoform were used. Amplification of cDNA for each receptor was undertaken using cDNA of human brain cortex, caudate nucleus or white blood cells as a positive control.…”
Section: Rna Extraction and First Strand Cdna Synthesismentioning
confidence: 99%
“…LSD binds to 5-HT receptors including 5-HT 2A and 5-HT 7 , both of which are expressed in the platelet (Cook et al, 1994) (Cook EH, unpublished observation). Murphy et al (2006) recently described decreased cortical 5-HT 2A binding in Asperger's syndrome, supporting the possible relevance of the platelet model.…”
Section: Introductionmentioning
confidence: 99%